Mitolojik Kadın Figürü Ve Dergi Kapaklarındaki Göstergeler - Demircan, Melda (The Turkish Online Journal of Design, Art and Communication, 2013)
In this study the emphasized identity of woman will be examined by comparing the woman image in different magazine covers. In this context the relationship and similarities between the woman celebrities’ images that exists on magazine covers and the woman images in ancient Greek mythology will be analyzed with semiological approach. Woman became strong representative of the consumption culture as a result of transforming the aesthetic value of the woman body and the woman sexuality to a consumption object. And this will be explained by interpreting the pictured structures of the visual signs and mythological female heroes in art.
Keywords: Woman image; Mythology; Sign; Magazine Cover Design; Kadın Görüntü; Mitoloji; İşaret; Dergi Kapağı Tasarımı